2012
DOI: 10.1029/2011wr011564
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a large fluvial island, streambed, and stream bank on surface water‐groundwater fluxes and water table dynamics

Abstract: [1] Substantial research on how hydraulic and geomorphologic factors control hyporheic exchange has resulted in reasonable process understanding; however, the role of fluvial islands on the transient nature of spatial flux patterns remains elusive. We used detailed field observations of the Truckee River, Nevada from 2003 to 2009 to quantify fluid flux between the river and a fluvial island, the streambed, and the adjacent stream bank. We constructed a 3-D numerical flow and heat transport model to further qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 64 publications
5
40
0
Order By: Relevance
“…Research by Shope et al (2012) confirms this observation. The lowest downwelling was seen at cable section 111 m, a section of the cable buried in a shallow pool of stagnant water at the side of the stream.…”
Section: Discussionsupporting
confidence: 77%
“…Research by Shope et al (2012) confirms this observation. The lowest downwelling was seen at cable section 111 m, a section of the cable buried in a shallow pool of stagnant water at the side of the stream.…”
Section: Discussionsupporting
confidence: 77%
“…In fact, despite differences in space and timescales, the results in Duque et al () were synthesized in a conceptual model that is similar to ours (compare our Figure with their figure 9). Shope et al () presented observations at a timescale that was more similar to our study. They found that temperature throughout a large bar (~200 m long and ~60 m wide) can change drastically within a few hours during inundation.…”
Section: Discussionsupporting
confidence: 89%
“…Bedform-induced hyporheic exchanges can be viewed as longitudinally 2-D vertical processes. Similar 2-D horizontal processes also occur in single or alternating unit bars (Burkholder et al, 2008;Cardenas, 2009a;Deforet et al, 2009;Derx et al, 2010;Marzadri et al, 2010;Shope et al, 2012) or bedform discontinuities (Hester and Doyle, 2008).…”
Section: Morphological Shaping Related To the Hydro-sedimentary Rivermentioning
confidence: 99%